THE IMPLEMENTATION OF THE DPRD RECESS POLICY IN ABSORBING PUBLIC ASPIRATIONS (A CASE STUDY OF THE REGIONAL HOUSE OF REPRESENTATIVES OF NORTH SUMATRA PROVINCE, ELECTORAL DISTRICT VII) - Roby Agusman Harahap; Audia Junita; Beby Masitho Batubara (Pena Cendekia Insani, 2026)
This study aims to analyze the implementation of the Regional House of Representatives (DPRD) recess policy in absorbing public aspirations in Electoral District VII of the Regional House of Representatives of North Sumatra Province. This research employs a qualitative approach using a descriptive-analytical method. Data were collected through in-depth interviews, documentation studies, and source triangulation involving informants consisting of DPRD members, the DPRD Secretariat, related regional government agencies, and community representatives. The analysis applies George C. Edward III’s policy implementation model, which emphasizes the aspects of communication, resources, disposition, and bureaucratic structure. The findings indicate that the implementation of the recess has been carried out in accordance with formal provisions; however, its effectiveness in absorbing and following up public aspirations still faces several challenges. Limitations in time and budget, as well as the complexity of inter-agency coordination, affect the optimal integration of aspirations into regional planning and budgeting documents. In addition, not all public aspirations can be accommodated due to differences in development priorities and limitations of authority.